Analisis Faktor-Faktor Yang Berpengaruh Pada Penghindaran Pajak : (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019) - Rizky Oktaviana; Lihan Rini Puspo Wijaya; Dian Nirmala Dewi (Jurnal Ilmiah ESAI, 2022)
The purpose of this study is to find out the factors influencing Tax Avoidance such as Capital Intensity, Firm Size, Leverage, Return On Assets (ROA), and Sales Growth. The population of this study includes all manufacturing companies in various sectors listed on the Indonesia Stock Exchange (IDX). By using purposive sampling technique with predetermined criteria, there are 50 companies as samples during 2017-2019. All of data required are obtained from IDX website. Multiple regression analysis is run with tax avoidance as the dependent variable, while capital intensity, firm size, leverage, return on assets (ROA), and sales growth as independent variables. The results of the test show that return on assets (ROA) had an effect on tax avoidance, while capital intensity, firm size, leverage, and sales growth had no effect on tax avoidance.